Quality Characteristics of Banana Chips and Oils After Deep Fat Frying - Ammawath, Wanna (2002)
B anana chips prepared from Pisang Abu and Pisang Nangka at "green" and 'trace of yellow' stages of ripeness were studied. The results showed that A bu had higher carbohydrate content than Nangka at both stages of maturities. The fruits were peeled, sliced and deep-fried in refined, bleached and deodorised (RBD) palm olein at 180 ± 5°C for 3 min. The moisture content and water activity (av.) of Abu chips were lower than those of Nangka. Sensory evaluation showed that chips prepared from Abu at both stages of ripeness were better in all characteristics. The Abu was selected and used in the subsequent study. The effects of deep-fat-frying in RBD palm olein and soybean oil were studied. Before the frying process, the A bu banana was subjected to three different pretreatment methods.as fol lows: (i) peeled and sliced banana (control), (ii) blanched whole green banana in water at 70°C for 20 min and (iii) whole banana soaked sodium chloride (NaCI) solution for 30 min. RBD palm olein was shown to be more stable to oxidation than soybean oil while there was no difference i n the different pretreatment methods in both oils. The result also indicated that banana soaked in NaCI solution and fried in RBD palm olein presented better sensory score in colour, flavour, odour, texture and overall acceptance attributes while the texture of control banana fried in RBD palm olein showed better crispness than the other samples. Storage study using four types of packaging materials namely, laminated aluminium foil (LAF), oriented polypropylene (OPP), polypropylene (PP), and low density polyethylene (LOPE) was also conducted. The parameter determined were moisture content, water activity (aw), thiobarbituric acid reaction substances (TBARS), crispness, colour and sensory properties of banana chips. The results showed that samples packed in LAF gave lower moisture content, aw and TBARS values and higher in sensory score on crispness, colour and rancid-odour descriptors than the other three samples during 8 weeks storage times. It was clear that the most notable changes during storage were samples packed in LOPE which gave the lowest score in crispness and product colour. The changes in quality of RBO palm olein with added oc-tocopherol, oleoresin rosemary and thei r com bination during deep-fat frying were also studied. The finding of this study reveals that RBO palm olein with added antioxidant showed significantly (P<0.05) lower in peroxide value, anisidine value, totox value, E 1%lcm at 232 nm and 268 nm, free fatty acid and v iscosity. In general oleoresin rosemary was more effective in retarding oxidative deterioration after 5 days of frying.